2015
DOI: 10.1111/ejed.12147
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Education and Training: Researching the Relationship between School and Work

Abstract: IntroductionDevelopments in society, and more specifically in labour markets, such as an ageing workforce, high rates of youth unemployment, skills shortages, and flexicurity have an impact on societal demands on vocational education and training (VET). Employees who are professional, flexible, and employable, who have the necessary competences, and who are capable of lifelong learning (OECD, 2014) are needed. In this regard, VET plays a key role in their preparation. The relationship between school and work i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
17
0
4
Order By: Relevance
“…Regarding learning at work, the work environment is the learning context (Mulder, Messmann, & König, 2015). Individuals learn at work by doing the work itself, by interacting with colleagues, by coping with challenges or by reflecting on experiences.…”
Section: Learning At Workmentioning
confidence: 99%
“…Regarding learning at work, the work environment is the learning context (Mulder, Messmann, & König, 2015). Individuals learn at work by doing the work itself, by interacting with colleagues, by coping with challenges or by reflecting on experiences.…”
Section: Learning At Workmentioning
confidence: 99%
“…Nám í skóla og á vinnustað baetir hvort annað upp með ólíkum námstaekifaerum, laerdómi og reynslu nemenda á hvorum vettvangi fyrir sig (sjá t.d. Aarkrog, 2005;Billett, 2009;Eraut, 2004;Fuller og Unwin, 2004b;Griffiths og Guile, 2003;Schaap, Baartman og de Bruijn, 2012), en árangur byggist að miklu leyti á því hvernig gengur að tryggja samhengi í náminu í skólanum og á vinnustaðnum (Billett, 2014;Mulder, Messmann og König, 2015;Schaap o.fl., 2012;Sloane, 2014;Tynjälä, 2008). Markmið rannsóknarinnar er skoða hvernig samspili náms í skóla og á vinnustað er háttað og hvort námið í heild myndar samfellu og samhengi.…”
Section: Inngangurunclassified
“…Research has, however, also shown that the effectiveness of the dual system is in part based on the coherence of the learning that takes place at each site. Transfer of learning from the school to the workplace and vice versa is often elusive, and students have difficulty making sense of how what they learn at school is relevant to work and how experiences at the workplace relate to what is discussed at school (Billett, 2013(Billett, , 2014Guile & Young, 2004;Mulder, et al, 2015;Schaap, et al, 2012;Sloane, 2014;Tynjälä, 2008;Wahlgren, 2009). The goal of the research was to investigate how the dual system in the certified trades (where a journeyman's examination is required for working in the trade) is implemented in Iceland and, specifically, to look at whether the system provides a coherent educational experience in terms of how educational pathways are organized.…”
Section: Introductionmentioning
confidence: 99%
“…En efecto, el tipo de relación entre la educación y el trabajo constituye una de las características clave que determinaría la calidad de la formación técnica de un sistema educativo(Mulder et al, 2015), siendo el principal elemento distintivo del liderazgo directivo en la educación técnico profesional. Este vínculo otorga el marco de acciones generales para cada uno de los siguientes factores, así como también las habilidades de liderazgo que cada uno de estos demanda a quienes desempeñan tareas directivas en contextos técnico profesionales.…”
unclassified
“…La relación entre educación y trabajo constituye un elemento transversal de la formación técnico profesional, pero las formas en que esta se despliega varían de acuerdo con las lógicas de cada país y obedecen a contextos más amplios como las políticas de bienestar, el grado de centralización de los países, los marcos institucionales de la educación y los mecanismos de regulación de los mercados laborales, entre otros. De acuerdo conMulder et al (2015) para comprender la naturaleza de la relación entre educación y trabajo es fundamental la consideración de los contextos históricoculturales, políticos e institucionales de cada sistema de formación en particular.5 Centro Europeo para el Desarrollo de la Formación Profesional, Unión Europea. Este documento sintetiza los principales esfuerzos de coordinación de la oferta actual de la educación y formación para el trabajo a nivel europeo y que incide de manera significativa en las orientaciones de política para los centros de formación en diferentes lugares del mundo.…”
unclassified